2007
DOI: 10.1007/s11547-007-0176-y
|View full text |Cite
|
Sign up to set email alerts
|

Ecografia ad alta risoluzione nella patologia cistica meniscale del ginocchio: nostra esperienza

Abstract: HRUS is a fairly reliable technique in the detection, characterisation and differentiation of the different forms of meniscal cyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…In the 15 studies where it was stated the mean age of the cohorts was 38.5 (SD 10.4) [ 102 104 , 108 , 110 113 , 115 121 ]. Mean time from injury to imaging was not stated in 14 studies [ 102 104 , 106 109 , 111 , 113 115 , 117 , 119 , 120 ]. In the six studies where this was stated [ 110 , 112 , 116 , 118 , 119 , 121 ], it ranged from 3.3 days [ 112 ] to 6 months [ 110 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 15 studies where it was stated the mean age of the cohorts was 38.5 (SD 10.4) [ 102 104 , 108 , 110 113 , 115 121 ]. Mean time from injury to imaging was not stated in 14 studies [ 102 104 , 106 109 , 111 , 113 115 , 117 , 119 , 120 ]. In the six studies where this was stated [ 110 , 112 , 116 , 118 , 119 , 121 ], it ranged from 3.3 days [ 112 ] to 6 months [ 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies did not report on who performed and reviewed the ultrasound images [ 113 , 118 ]. In the 18 studies where this was reported, 16 studies recorded a radiologist performed and interpreted the images [ 102 109 , 111 , 112 , 114 117 , 119 , 120 ] and in two studies a non-radiologist performed and interpreted the images [ 110 , 121 ]. The non-radiologists were a sonographer and a physician [ 110 , 121 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rutten et al [ 11 ] demonstrated the sensitivity, specificity, and accuracy of ultrasound in the depiction of meniscal cysts as 97, 86, and 94%, respectively, with a positive predictive value of 94% and a negative predictive value of 92%. Sorrentino et al found that high-resolution ultrasound had a sensitivity, specificity, PPV, and NPV of 94.23%, 100%, 100%, and 94.54%, respectively, for the detection of meniscal cysts [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The more common consensus among authors is that meniscal cysts are far more frequently encountered laterally at an incidence of 75% to 90% [1]. This may be in part related to the relative weakness of the lateral meniscocapsular attachments when compared to the more tightly adherent medial meniscocapsular junction [3]. According to one study, lateral meniscal cysts tend to occur just anterior to the lateral collateral ligament, through a region of inherent weakness, and are more likely to reach a larger size [3].…”
Section: Case Reportmentioning
confidence: 99%
“…This may be in part related to the relative weakness of the lateral meniscocapsular attachments when compared to the more tightly adherent medial meniscocapsular junction [3]. According to one study, lateral meniscal cysts tend to occur just anterior to the lateral collateral ligament, through a region of inherent weakness, and are more likely to reach a larger size [3]. In contrast, medial meniscal cysts are thought to be confined with limited expansion by firmer meniscocapsular tissue, only reaching larger sizes after violating the capsule and potentially extending for some distance from the meniscus [1].…”
Section: Case Reportmentioning
confidence: 99%